Problems of training competitive higher education graduates in today’s environment - G. N. Ryazanova (Вестник университета)
One of the drivers of economic development is human capital, which can transform the economic space and reveal the innovative potential of the socio-economic landscape’s systems and subsystems. The key role in shaping the human resources of the future belongs to the higher school. Current institutional conditions impose new requirements on graduates of higher educational institutions and to the higher education system, in particular, to university teachers. Purpose of the study: to reveal the necessary competencies of a modern teacher of the Higher School, necessary for the preparation of competitive specialists and managers. The article uses historical, logical and comparative research methods, systems approach and modelling method. The author substantiates the factors, influencing the transformation of the modern ecosystem and the modern student, the characteristic features of students at universities, identifies the, and indicates on need to change the mission of the higher school and the teacher. A list of key competencies of a lecturer and seminarian of the higher school, which helps him to prepare the competitive graduate, was highlighted.